Integrated multi‐omics profiling of high‐grade estrogen receptor‐positive, HER2‐negative breast cancer. Issue 12 (29th July 2021) - Wang, Kang; Li, Lun; Franch‐Expósito, Sebastià; Le, Xin; Tang, Jun; Li, Qing; Wu, Qianxue; Bassaganyas, Laia; Camps, Jordi; Zhang, Xiang; Li, Hongyuan; Foukakis, Theodoros; et al.
Abstract : Estrogen receptor‐positive and human epidermal growth factor receptor 2‐negative (ER + HER2 − ) breast cancer accounts for 60–70% of all cases of invasive breast carcinoma. High‐grade ER + HER2 − tumors respond poorly to endocrine therapy. In this study, we systematically analyzed clinical and multi‐omics data to find potential strategies for personalized therapy of patients with high‐grade ER + HER2 − disease. Six different cohorts were analyzed, for which multi‐omics data were available. Grade III ER + HER2 − cases harbored higher proportions of large tumor size (> 5 cm), lymph node metastasis, chemotherapy use, and luminal B subtypes defined by PAM50, as compared with grade I/II tumors. DNA methylation (HM450) data and methylation‐specific PCR indicated that the cg18629132 locus in the MKI67 promoter was hypermethylated in grade I/II cases and normal tissue, but hypomethylated in grade III cases or triple‐negative breast cancer, resulting in higher expression of MKI67 . Mutations in ESR1 and TP53 were detected in post‐endocrine treatment metastatic samples at a higher rate than in treatment‐naive tumors in grade III cases. We identified 42 and 20 focal copy number events in nonmetastatic and metastatic high‐grade ER + HER2 − cases, respectively, with either MYC or MDM2 amplification representing an independent prognostic event in grade III cases. Transcriptional profiling within grade III tumors highlighted ER signaling downregulation and upregulation of immune‐related pathways in non‐luminal‐like tumors defined by PAM50. Recursive partitioning analysis was employed to construct a decision tree of an endocrine‐resistant subgroup (GATA3‐negative and AGR‐negative) of two genes that was validated by immunohistochemistry in a Chinese cohort. All together, these data suggest that grade III ER + HER2 − tumors have distinct clinical and molecular characteristics compared with low‐grade tumors, particularly in cases with non‐luminal‐like biology. Due to the dismal prognosis in this group, clinical trials are warranted to test the efficacy of potential novel therapies. Abstract : High histologic grade is associated with significantly increased risk of breast cancer‐specific mortality among patients with ER + HER2 − tumors, but the cause for worse outcomes in this subset remains unknown. Here, we integrated the multi‐omics data to reveal important biomarkers, therapeutic targets, and precision medicine strategy for grade III ER + HER2 − breast cancer patients.